Comparison of anthelmintic and anti-bacterial agents fed weanling pigs reared on pasture - B A Koch; S M Kruckenberg; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1977)
Forty-eight Yorkshire pigs averaging 35 lbs. were used to compare their performance under these feeding sequences: (A) mecadox plus banminth, received until weighing 75 lbs., followed by terrarnyci n to 125 lbs.; (B) worming with tramisol initially and feeding ASP-250 until weighing 125 lbs. To market weight, pigs in both treatment groups were fed a nonmedicated finisher diet. Rate of gain was similar for both treatments; the sequence A pigs, however, required 6% fewer lbs. of feed per pound of gain. Pigs fed banminth had, after 35 days, no ascarid scars in their livers and no ascarids in their intestines. Pigs wormed initially with tramisol had livers with 40 to 50 ascarid scars (both diaphragmatically and viscerally), and one pig had nine ascarids in his intestine. For pigs slaughtered at 125 lbs. and market weight, we observed fewer liver scars and intestinal ascarids in those wormed with banminth than with tramisol.; Swine Day, Manhattan, KS, November 10, 1977
Keywords: Swine day; 1977; Kansas Agricultural Experiment Station contribution; no. 78-101-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 312; Swine; Anthelmintic; Anti-Bacterial agents; Weanling pigs; Pasture